1998
DOI: 10.2190/c670-y3c8-ltj1-ct3p
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of Scores on a Computer Programming Self-Efficacy Scale and Group Analyses of Novice Programmer Self-Efficacy

Abstract: Self-efficacy theory was applied to the domain of computer programming to develop a thirty-two-item self-efficacy scale for computer programming, primed to the C++ programming language. To assess its construct validity, the scale was administered to 421 students enrolled in an introductory course in C++ programming at the beginning and the end of the course. The reliability of the scores was high. An exploratory factor analysis, with oblimin rotation, yielded a four-factor solution. There was a growth in self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
127
0
14

Year Published

2005
2005
2021
2021

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 213 publications
(146 citation statements)
references
References 25 publications
5
127
0
14
Order By: Relevance
“…Self-efficacy was measured using the Computer Programming Self-Efficacy Scale [35]. This validated instrument has been used previously in research on success factors in introductory computer science courses [34,52].…”
Section: Methodsmentioning
confidence: 99%
“…Self-efficacy was measured using the Computer Programming Self-Efficacy Scale [35]. This validated instrument has been used previously in research on success factors in introductory computer science courses [34,52].…”
Section: Methodsmentioning
confidence: 99%
“…Group efficacy in computer-mediated virtual groups has begun to receive more attention [13,17] but is not well studied yet. It is worthwhile to make further exploration to see how group efficacy develops over time and how it indicate technology impact and group outcomes in different collaborative modes of virtual working.…”
Section: Asynchronous Vs Multi-synchronous Virtual Teamsmentioning
confidence: 99%
“…Although both self-and group efficacy are widely recognized in many fields, in human-computer interaction community, efficacy theories have been largely unnoticed [11]. Ramalingam et al reported that self-efficacy in computing could be used as a predictor of technology learning and achievement [17]. Recent work has begun to make explorations into group efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…The Computer Programming Self-efficacy scale was designed by Ramalingham and Wiedenbeck (1998) and consists of 33 items which ask students to judge their capabilities in a wide range of programming tasks and situations. As this instrument was administered when students had very limited experience of the module material, a shortened version of this scale using only seven questions was used.…”
Section: Instrumentsmentioning
confidence: 99%